Determination of velogenic Newcastle disease virus strain tissue tropism and disease pathogenesis by application of immunoperoxidase staining andin situ PCR - Mahmoud, Hussein Abdallah Elawad; Bejo, Mohd Hair; Omar, Abdul Rahman; Arshad, Siti Suri; Ideris, Aini (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2015)
Twenty four, 3-week-old specific pathogen free (SPF) chickens were infected with 10⁵ EID50/0.1 mL of velogenic Newcastle disease virus (vNDV) AF2240 isolate intra-nasally, and 15 SPF chickens were remained uninfected and acted as the control group. The chickens were sacrificed at various intervals through the trial. Samples of brain, trachea, lung, caecal tonsils, liver, kidney, spleen, heart, proventriculus, intestine, bursa of Fabricius and thymus were fixed in 10% buffered formalin, processed, and embedded in paraffin for immunoperoxidase staining (IPS) and in situ PCR examination. The study showed that following intranasal inoculation of vNDV in SPF chickens, the virus enter the trachea; respiratory tract. At the same time virus was also enter the caecal tonsils, intestine and bursa of Fabricus either through the direct contact from the intestinal lumen or primary viraemia. During the primary viraemia, the virus enter most of the organs examined, including the brain at 6 hours pi. It appears that secondary viraemia occurred as early as 12 hours pi when all samples of the organs examined were positive for the virus by in situ PCR. The main primary tissue tropism for vNDV is the trachea; tracheal or bronchial associated lymphoid tissues (BALT) followed by caecal tonsils; gastrointestinal tract associated lymphoid tissues (GALT). The virus also caused infection into the brain, the central nervous system. It was concluded that the in situ PCR and IPS techniques applied in the present study could determine the pathogenesis and tissue tropism of vNDV following intranasal inoculation of the virus in SPF chickens.